Gender, Jewish Identity, and Cultural Memory in the Poetry of Rhea Tregebov - Hollenberg, Donna Krolik (Canadian Jewish Studies / Études juives canadiennes, 2003)
Rhea Tregebov’s self consciousness as a woman facilitated her developing self consciousness as a Canadian Jew, a process recorded in her five books of poetry. In the course of this work, her reflections on the social meanings of motherhood are particularly important. When insights about the parent-child bond are transferred to reflections about the meanings of modern Jewish history, particularly the Holocaust, the poet’s understanding of her role is extended. The result is an ambitious collection of elegies in which she changes the structure of mourning specific to that genre.